The Role of Parasites in Acute Appendicitis of Pediatric Patients - Dorfman, Saul; Cardozo, José; Dorfman, Denny; Del Villar, Alonso (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> There is little evidence regarding the relationship between parasites and acute appendicitis. In order to determine such a relationship, if any, 830 appendectomy specimens were studied. Age, sex, pathological findings and the presence and type of parasites and the type of parasite were analyzed. Parasites were present in 62 cases (7.46%). Ascaris lumbricoides and Trichuris trichiura were the most frequently encountered parasites. These were observed, alone or in combination, in 45 cases (72.5%). Appendix perforation, peritonitis, necrosis and flegmonous appearance, were more frequent in the cases of acute appendicitis without parasitic infestation (p < 0.05). There were no differences between the cases with or without parasitic infestation (p > 0.05) In cases of peritonitis. The low incidence of parasites among the appendectomy specimens and the failure to demonstrate its relationship with all events derived of appendicitis, do not support the hypothesis that parasites are a major cause of appendicitis in pediatric patients